(untitled) (مجلة المنصور, 2023)
RA is an autoimmune illness that is most common in women, suggesting that female hormone variations have a role in disease progression. Knowing how they affect the development of RA is clinically relevant and might help with specialized prevention initiatives in high-risk individuals. The goal of this study was to look at the relationship between menopause and inflammatory markers with RA disease progression. This is a case-control study carried out on 300 RA patients; they were diagnosed by rheumatology specialists during the period from September 2021 to January 2022 then tested for RF, CRP, ESR and ACCP. The findings revealed that 88% of patients had positive ACCP results, whereas 71% had positive RF results, and 97% had positive CRP values. The majority of rheumatoid arthritis patients 66.7% (200/300) were in their postmenopausal period, while 33.4% (100/300) were in their premenopausal stage when they were diagnosed. The findings revealed that postmenopausal RA women had more severe disease activity than premenopausal RA women, as evidenced by the elevated Das28 and ESR values, (4.63 ± 0.10) and (47.14 ± 0.69) respectively, in comparison to their lower levels (3.66 ± 0.09) and (36.12 ± 0.81) in premenopausal RA patients. Both groups, however, had elevated levels in contrast to the control group.